Hydration Changes upon DNA Folding Studied by Osmotic Stress Experiments - Nakano, Shu-ichi (The Biophysical Society, 2012)
The thermal stability of nucleic acid structures is perturbed under the conditions that mimic the intracellular environment, typically rich in inert components and under osmotic stress. We now describe the thermodynamic stability of DNA oligonucleotide structures in the presence of high background concentrations of neutral cosolutes. Small cosolutes destabilize the basepair structures, and the DNA structures consisting of the same nearest-neighbor composition show similar thermodynamic parameters in the presence of various types of cosolutes. The osmotic stress experiments reveal that water binding to flexible loops, unstable mismatches, and an abasic site upon DNA folding are almost negligible, whereas the binding to stable mismatch pairs is significant. The studies using the basepair-mimic nucleosides and the peptide nucleic acid suggest that the sugar-phosphate backbone and the integrity of the basepair conformation make important contributions to the binding of water molecules to the DNA bases and helical grooves. The study of the DNA hydration provides the basis for understanding and predicting nucleic acid structures in nonaqueous solvent systems.